Overlaminate film for license plates and license plates

JP7939924B2Active Publication Date: 2026-10-22NIPPON CARBIDE KOGYO KK
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023180539
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-10-19
Publication Date
2026-10-22
Estimated Expiration
2043-10-19

AI Technical Summary

Benefits of technology

【0007】 本開示の一実施形態によれば、被着体に対して高い粘着力を有し、かつ、三次元成形の際に外観不良を生じさせ難い粘着剤層を形成できるオーバーラミネートフィルム用粘着剤組成物が提供される。 本開示の他の実施形態によれば、上記オーバーラミネートフィルム用粘着剤組成物により形成された粘着剤層を備えるオーバーラミネートフィルム及びナンバープレートが提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007939924000010
    Figure 0007939924000010
  • Figure 0007939924000011
    Figure 0007939924000011
  • Figure 0007939924000012
    Figure 0007939924000012
Patent Text Reader

Abstract

To provide an adhesive composition for overlaminate films, enabling formation of an adhesive layer that exhibits strong adhesion to adherends and is less prone to cause visual defects during three-dimensional molding.SOLUTION: The present invention provides an adhesive composition for overlaminate films, comprising: a (meth)acrylic copolymer (A), a (meth)acrylic copolymer (B), and an epoxy-based or isocyanate-based crosslinking agent, wherein the (meth)acrylic copolymer (A) contains 1 to 15 mass% of structural units derived from a monomer having a carboxyl group, and has a glass transition temperature (Tg) of -45°C to -5°C; the (meth)acrylic copolymer (B) contains structural units derived from a monomer having an amino group, and has a Tg of 50°C to 100°C; the content of the (meth)acrylic copolymer (B) is 5 to 25 pts.mass based on 100 pts.mass of the (meth)acrylic copolymer (A); and the molar ratio of crosslinkable functional groups in the crosslinking agent to carboxyl groups in the (meth)acrylic copolymer (A) is within a predetermined range.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a pressure-sensitive adhesive composition for overlaminate films, an overlaminate film, and a license plate.

Background Art

[0002] Conventionally, films subjected to inkjet printing have been used for decorating outdoor signs, vehicles (for example, motorcycles and four-wheeled vehicles), and the like. Such a film has a configuration including at least a printing film for performing printing and an overlaminate film for protecting the printing film, and in recent years, it has also been used for license plates (also referred to as "number plates") (see, for example, Patent Documents 1 to 4).

Prior Art Documents

Patent Documents

[0003]

Patent Document 1

Patent Document 2

Patent Document 3

Patent Document 4

Summary of Invention

Problems to be Solved by the Invention

[0004] By the way, although generally used overlaminate films have excellent adhesion to adherends, cohesive failure of the pressure-sensitive adhesive layer occurs around the convex portions of the adherend during three-dimensional forming, which may become a factor impairing the appearance.

[0005] The present disclosure has been made in view of the circumstances as described above. The problem that one embodiment of this disclosure aims to solve is to provide an adhesive composition for overlaminate films that has high adhesive strength to the adherend and can form an adhesive layer that is less likely to cause appearance defects during three-dimensional molding. Other embodiments of this disclosure aim to solve the problem of providing an overlaminate film and a license plate having an adhesive layer formed by the above-described adhesive composition for overlaminate films. [Means for solving the problem]

[0006] The following are examples of specific means for solving the problem: <1> (Meth)acrylic copolymer (A), (meth)acrylic copolymer (B), epoxy crosslinking agent, Includes, The (meth)acrylic copolymer (A) contains constituent units derived from monomers having carboxyl groups in a proportion of 1% to 15% by mass relative to the total constituent units of the (meth)acrylic copolymer (A), and has a glass transition temperature of -45°C to -5°C. The (meth)acrylic copolymer (B) contains constituent units derived from monomers having at least one amino group selected from the group consisting of primary amino groups, secondary amino groups, and tertiary amino groups, and has a glass transition temperature of 50°C to 100°C. The content of the (meth)acrylic copolymer (B) is 5 to 25 parts by mass per 100 parts by mass of the (meth)acrylic copolymer (A), An adhesive composition for overlaminate films, wherein the ratio of the number of moles of epoxy groups in the epoxy crosslinking agent to the number of moles of carboxyl groups in the (meth)acrylic copolymer (A) is 0.0045 or more. <2> (Meth)acrylic copolymer (A), (meth)acrylic copolymer (B), and isocyanate crosslinking agent, Includes, The (meth)acrylic copolymer (A) contains constituent units derived from monomers having carboxyl groups in a proportion of 1% to 15% by mass relative to the total constituent units of the (meth)acrylic copolymer (A), and has a glass transition temperature of -45°C to -5°C. The (meth)acrylic copolymer (B) contains constituent units derived from monomers having at least one amino group selected from the group consisting of primary amino groups, secondary amino groups, and tertiary amino groups, and has a glass transition temperature of 50°C to 100°C. The content of the (meth)acrylic copolymer (B) is 5 to 25 parts by mass per 100 parts by mass of the (meth)acrylic copolymer (A), An adhesive composition for overlaminate films, wherein the ratio of the number of moles of isocyanate groups in the isocyanate crosslinking agent to the number of moles of carboxyl groups in the (meth)acrylic copolymer (A) is 0.1 to 0.5. <3> The weight-average molecular weight of the (meth)acrylic copolymer (A) is between 400,000 and 2,500,000. <1> or <2> The adhesive composition for overlaminate film described in [reference]. <4> The weight-average molecular weight of the (meth)acrylic copolymer (B) is between 0.5 million and 200,000. <1> ~ <3> An adhesive composition for overlaminate film as described in any one of the items. <5> The total content of constituent units derived from the monomer having the amino group in the (meth)acrylic copolymer (B) is 1.5% by mass or more relative to the total constituent units of the (meth)acrylic copolymer (B). <1> ~ <4> An adhesive composition for overlaminate film as described in any one of the items. <6> Surface protective film, It is provided on one side of the aforementioned surface protective film, and <1> ~ <5> An adhesive layer formed with an adhesive composition for overlaminate film as described in any one of the items, An overlaminate film equipped with [specific feature]. <7> The surface protective film includes a polyurethane resin. <6> The overlaminate film described above. <8> Plate substrate and The overlaminate film according to <6> or <7> provided on one surface side of the plate base material, and A license plate comprising the same.

Effects of the Invention

[0007] According to one embodiment of the present disclosure, there is provided a pressure-sensitive adhesive composition for overlaminate films, which has high adhesive strength to an adherend and can form a pressure-sensitive adhesive layer that hardly causes appearance defects during three-dimensional forming. According to another embodiment of the present disclosure, an overlaminate film and a license plate comprising a pressure-sensitive adhesive layer formed from the above pressure-sensitive adhesive composition for overlaminate films are provided.

Brief Description of the Drawings

[0008] [Figure 1] It is a schematic cross-sectional view showing an example of the configuration of the overlaminate film of the present disclosure. [Figure 2] It is a schematic cross-sectional view showing an example of the configuration of the license plate of the present disclosure. [Figure 3] It is a schematic cross-sectional view showing an example of another configuration of the license plate of the present disclosure. [Figure 4A] It is a photograph showing an example of the evaluation result "A" of cohesive failure in Examples. [Figure 4B] It is a photograph showing an example of the evaluation result "B" of cohesive failure in Examples. [Figure 4C] It is a photograph showing an example of the evaluation result "C" of cohesive failure in Examples. [Figure 5] It is a diagram schematically showing the mold used for embossing in the strain evaluation test in Examples.

Modes for Carrying Out the Invention

[0009] Hereinafter, the pressure-sensitive adhesive composition for overlaminate films, the overlaminate film, and the license plate of the present disclosure will be described in detail. The description of the requirements set forth below may be made based on representative embodiments of the present disclosure, but the present disclosure is not limited to such embodiments, and can be implemented with appropriate modifications within the scope of the purpose of the present disclosure.

[0010] In the present disclosure, a numerical range indicated by using "~" means a range including the numerical values stated before and after "~" as the lower limit value and the upper limit value, respectively. In the numerical ranges described stepwise in the present disclosure, an upper limit value or a lower limit value described in a certain numerical range may be replaced with an upper limit value or a lower limit value of another stepwise described numerical range. Further, in the numerical ranges described in the present disclosure, an upper limit value or a lower limit value described in a certain numerical range may be replaced with a value shown in the Examples.

[0011] In the present disclosure, a combination of two or more preferred embodiments is a more preferred embodiment.

[0012] In the present disclosure, the amount of each component in the pressure-sensitive adhesive composition for overlaminate films means, when a plurality of substances corresponding to each component are present in the pressure-sensitive adhesive composition for overlaminate films, the total amount of the plurality of substances present in the pressure-sensitive adhesive composition for overlaminate films, unless otherwise specified.

[0013] In the present disclosure, the term "(meth)acrylic monomer" means a monomer having a (meth)acryloyl group. In the present disclosure, the term "(meth)acrylic copolymer" means a copolymer that includes structural units derived from a (meth)acrylic monomer, and in which the proportion of the structural units derived from the (meth)acrylic monomer is 50% by mass or more.

[0014] In this disclosure, "(meth)acrylic" is a term that encompasses both "acrylic" and "methacrylic," "(meth)acrylate" is a term that encompasses both "acrylate" and "methacrylate," and "(meth)acryloyl" is a term that encompasses both "acryloyl" and "methacryloyl."

[0015] In this disclosure, "n-" means normal, "i-" means iso, "s-" means secondary, and "t-" means tertiary.

[0016] In this disclosure, "mass%" and "weight%" are synonymous, and "parts by mass" and "parts by weight" are synonymous.

[0017] In this disclosure, the term "process" includes not only independent processes but also processes that cannot be clearly distinguished from other processes, as long as their intended purpose is achieved.

[0018] In this disclosure, "appearance defect" means an appearance defect caused by cohesive failure of the adhesive layer.

[0019] In this disclosure, "(meth)acrylic copolymer (A) and (meth)acrylic copolymer (B)" may be collectively referred to as "specific (meth)acrylic copolymer."

[0020] [Adhesive composition for overlaminate film] The first adhesive composition for overlaminate film of this disclosure (hereinafter also simply referred to as the "first adhesive composition") comprises a (meth)acrylic copolymer (A), a (meth)acrylic copolymer (B), and an epoxy crosslinking agent, wherein the (meth)acrylic copolymer (A) contains constituent units derived from monomers having carboxyl groups in a proportion of 1% to 15% by mass relative to the total constituent units of the (meth)acrylic copolymer (A), and has a glass transition temperature of -45°C to -5°C, and the (meth)acrylic copolymer (B) The (meth)acrylic copolymer (B) contains constituent units derived from a monomer having at least one amino group selected from the group consisting of primary amino groups, secondary amino groups, and tertiary amino groups, and has a glass transition temperature of 50°C to 100°C, the content of the (meth)acrylic copolymer (B) is 5 to 25 parts by mass per 100 parts by mass of the (meth)acrylic copolymer (A), and the ratio of the number of moles of epoxy groups in the epoxy crosslinking agent to the number of moles of carboxyl groups in the (meth)acrylic copolymer (A) is 0.0045 or more. Furthermore, the second adhesive composition for overlaminate film of this disclosure (hereinafter also simply referred to as the "second adhesive composition") comprises a (meth)acrylic copolymer (A), a (meth)acrylic copolymer (B), and an isocyanate crosslinking agent, wherein the (meth)acrylic copolymer (A) contains constituent units derived from monomers having carboxyl groups in a proportion of 1% to 15% by mass relative to the total constituent units of the (meth)acrylic copolymer (A), and has a glass transition temperature of -45°C to -5°C, and the (meth)acrylic copolymer (B) The (meth)acrylic copolymer (B) contains constituent units derived from a monomer having at least one amino group selected from the group consisting of primary amino groups, secondary amino groups, and tertiary amino groups, and has a glass transition temperature of 50°C to 100°C, the content of the (meth)acrylic copolymer (B) is 5 to 25 parts by mass per 100 parts by mass of the (meth)acrylic copolymer (A), and the ratio of the number of moles of isocyanate groups in the isocyanate crosslinking agent to the number of moles of carboxyl groups in the (meth)acrylic copolymer (A) is 0.1 to 0.5. Hereinafter, the first adhesive composition and the second adhesive composition may be collectively referred to as the "adhesive composition."

[0021] The adhesive composition of this disclosure contains, in a specific proportion, a combination of a (meth)acrylic copolymer (A) containing constituent units derived from monomers having carboxyl groups in a specific range of proportions and having a relatively low glass transition temperature, a (meth)acrylic copolymer (B) containing constituent units derived from monomers having amino groups and having a relatively high glass transition temperature, and an epoxy crosslinking agent or an isocyanate crosslinking agent as a crosslinking agent, thereby forming an adhesive layer that has high adhesive strength to the adherend and is less likely to cause appearance defects during three-dimensional molding. The reason why the adhesive composition of this disclosure may produce such effects is not clear, but the inventors speculate as follows. However, the following speculation is not intended to be interpreted restrictively to the adhesive composition of this disclosure, but is explained as an example.

[0022] The adhesive composition disclosed herein is used to form the adhesive layer of an overlaminate film. While the adhesive layer formed by conventional adhesive compositions for overlaminate films exhibits excellent adhesion to the substrate, cohesive failure may be observed around the convex parts of the substrate after three-dimensional molding following lamination. In contrast, the adhesive composition of this disclosure contains a (meth)acrylic copolymer (A) with a relatively low glass transition temperature, so the formed adhesive layer is expected to have excellent wettability to the adherend and adhere tightly to the adherend when bonded to it. For this reason, the adhesive layer formed by the adhesive composition of this disclosure can function suitably as the adhesive layer of an overlaminate film. Furthermore, the epoxy groups or isocyanate groups, which are crosslinkable reactive groups in the crosslinking agent, crosslink with the carboxyl groups in the (meth)acrylic copolymer (A). In the adhesive composition of this disclosure, the ratio of the number of moles of crosslinkable reactive groups in the crosslinking agent to the number of moles of carboxyl groups in the (meth)acrylic copolymer (A) is within a specific range, so it is considered that the cohesive force of the adhesive layer is increased to the extent that cohesive failure is suppressed. In addition, the presence of a (meth)acrylic copolymer with a high glass transition temperature is also effective in suppressing cohesive failure of the adhesive layer that may occur during three-dimensional molding. The (meth)acrylic copolymer (B) contained in the adhesive composition of this disclosure has a relatively high glass transition temperature and excellent compatibility with the (meth)acrylic copolymer (A) due to the presence of amino groups, and can therefore effectively function in suppressing cohesive failure of the adhesive layer that may occur during three-dimensional molding.

[0023] [(meth)acrylic copolymer (A)] The adhesive composition of this disclosure comprises a (meth)acrylic copolymer (A). (Meth)acrylic copolymer (A) contains constituent units derived from monomers having carboxyl groups in a proportion of 1% to 15% by mass relative to the total constituent units of (meth)acrylic copolymer (A), and has a glass transition temperature of -45°C to -5°C. The adhesive composition of this disclosure may contain only one (meth)acrylic copolymer (A), or it may contain two or more.

[0024] <Constituent units derived from monomers containing a carboxyl group> The (meth)acrylic copolymer (A) contains constituent units derived from monomers having a carboxyl group in a proportion of 1% to 15% by mass relative to the total constituent units of the (meth)acrylic copolymer (A). In this disclosure, "constituent unit derived from a monomer having a carboxyl group" means a constituent unit formed by the addition polymerization of monomers having a carboxyl group.

[0025] The type of monomer having a carboxyl group is not particularly limited. Examples of monomers having a carboxyl group include monomers having at least one carboxyl group and an ethylenically unsaturated group in one molecule. The ethylenically unsaturated group is not particularly limited and includes, for example, a vinyl group, an allyl group, a vinylphenyl group, a (meth)acrylamide group, and a (meth)acryloyl group. A (meth)acryloyl group is preferred as the ethylenically unsaturated group.

[0026] Specific examples of monomers having a carboxyl group include (meth)acrylic acid, crotonic acid, maleic acid, fumaric acid, itaconic acid, glutaconic acid, citraconic acid, ω-carboxy-polycaprolactone mono(meth)acrylate [e.g., ω-carboxy-polycaprolactone (n≒2) monoacrylate], and succinic acid derivatives (e.g., 2-acryloyloxyethyl succinic acid). As the monomer having a carboxyl group, a (meth)acrylic monomer having a carboxyl group is preferred, (meth)acrylic acid is more preferred, and acrylic acid is even more preferred.

[0027] The (meth)acrylic copolymer (A) may contain only one or more constituent units derived from monomers having a carboxyl group.

[0028] The content of constituent units derived from monomers having carboxyl groups in (meth)acrylic copolymer (A) is 1% to 15% by mass relative to the total constituent units of (meth)acrylic copolymer (A). When the content of constituent units derived from monomers having carboxyl groups in the (meth)acrylic copolymer (A) is 1% by mass or more relative to the total constituent units of the (meth)acrylic copolymer (A), the cohesive force of the adhesive layer is sufficiently increased, and cohesive failure of the adhesive layer around the protrusions of the adherend tends to be less likely to occur during three-dimensional molding. From this viewpoint, the content of constituent units derived from monomers having carboxyl groups in the (meth)acrylic copolymer (A) is preferably 2% by mass or more, more preferably 3% by mass or more, and even more preferably 4% by mass or more, relative to the total constituent units of the (meth)acrylic copolymer (A). When the content of constituent units derived from monomers having carboxyl groups in the (meth)acrylic copolymer (A) is 15% by mass or less relative to the total constituent units of the (meth)acrylic copolymer (A), the cohesive force of the adhesive layer does not become excessively high, and the decrease in the adhesive strength of the adhesive layer to the adherend tends to be suppressed. From this viewpoint, the content of constituent units derived from monomers having carboxyl groups in the (meth)acrylic copolymer (A) is preferably 10% by mass or less, more preferably 8% by mass or less, and even more preferably 6% by mass or less, relative to the total constituent units of the (meth)acrylic copolymer (A). In some embodiments, the content of constituent units derived from monomers having a carboxyl group in the (meth)acrylic copolymer (A) may be 1% to 10% by mass, 2% to 15% by mass, 2% to 10% by mass, 2% to 8% by mass, 3 to 10% by mass, 3% to 8% by mass, 3% to 6% by mass, 4% to 8% by mass, or 4% to 6% by mass, relative to the total constituent units of the (meth)acrylic copolymer (A).

[0029] <Constituent units derived from alkyl methacrylate monomers> The (meth)acrylic copolymer (A) preferably contains constituent units derived from alkyl (meth)acrylate monomers. In this disclosure, "constituent units derived from (meth)acrylate alkyl ester monomers" means constituent units formed by the addition polymerization of (meth)acrylate alkyl ester monomers. Furthermore, the term "(meth)acrylic acid alkyl ester monomer" in (meth)acrylic copolymer (A) does not include monomers that have a carboxyl group. In other words, if a monomer having a carboxyl group also falls under the category of (meth)acrylic acid alkyl ester monomer, it is classified as a monomer having a carboxyl group.

[0030] The type of alkyl (meth)acrylate monomer is not particularly limited. The alkyl acrylate monomer may be an alkyl acrylate monomer or an alkyl methacrylate monomer, but from the viewpoint of easily obtaining a (meth)acrylic copolymer (A) with a glass transition temperature of -45°C to -5°C, for example, an alkyl acrylate monomer is preferred. The alkyl group in the alkyl (meth)acrylate monomer may be unsubstituted or substituted, but it is preferable that it be unsubstituted. The alkyl group of the alkyl (meth)acrylate monomer may be linear, branched, or cyclic. The number of carbon atoms in the alkyl group of the (meth)acrylate monomer is preferably 1 to 18, more preferably 1 to 12, even more preferably 1 to 8, and particularly preferably 1 to 4.

[0031] Specific examples of alkyl (meth)acrylate monomers include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, n-octyl (meth)acrylate, i-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-nonyl (meth)acrylate, i-nonyl (meth)acrylate, n-decyl (meth)acrylate, stearyl (meth)acrylate, lauryl (meth)acrylate, cyclohexyl (meth)acrylate, and isobornyl (meth)acrylate. The alkyl (meth)acrylate monomer preferably contains at least one of methyl acrylate and n-butyl acrylate, and more preferably contains both methyl acrylate and n-butyl acrylate.

[0032] If the (meth)acrylic copolymer (A) contains constituent units derived from alkyl (meth)acrylate monomers, it may contain only one type of constituent unit derived from alkyl (meth)acrylate monomers, or it may contain two or more types.

[0033] When the (meth)acrylic copolymer (A) contains constituent units derived from alkyl (meth)acrylate monomers, the content of constituent units derived from alkyl (meth)acrylate monomers is not particularly limited, but for example, it is preferably 50% by mass or more, more preferably 50% to 99% by mass, even more preferably 60% to 97% by mass, and particularly preferably 70% to 96% by mass, relative to the total constituent units of the (meth)acrylic copolymer (A). Here, the content of constituent units derived from alkyl methacrylate monomers in (meth)acrylic copolymer (A) being 50% by mass or more relative to the total constituent units of (meth)acrylic copolymer (A) means that constituent units derived from alkyl methacrylate monomers are included as the main component of the constituent units of (meth)acrylic copolymer (A).

[0034] <Constituent units derived from other monomers> The (meth)acrylic copolymer (A) may contain constituent units derived from monomers that do not fall under either monomers having a carboxyl group or alkyl (meth)acrylate monomers (so-called other monomers). In this disclosure, "constituent units derived from other monomers" means constituent units formed by the addition polymerization of other monomers.

[0035] Other constituent units derived from monomers include, for example, constituent units derived from (meth)acrylates having aromatic rings, such as benzyl (meth)acrylate and phenoxyethyl (meth)acrylate; constituent units derived from alkoxyalkyl (meth)acrylates, such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate; constituent units derived from aromatic monovinyls, such as styrene, α-methylstyrene, t-butylstyrene, p-chlorostyrene, chloromethylstyrene, and vinyltoluene; constituent units derived from vinyl cyanides, such as acrylonitrile and methacrylonitrile; and constituent units derived from vinyl esters, such as vinyl formate, vinyl acetate, vinyl propionate, and vinyl versatate.

[0036] If the (meth)acrylic copolymer (A) contains constituent units derived from other monomers, it may contain only one type of constituent unit derived from other monomers, or it may contain two or more types.

[0037] If the (meth)acrylic copolymer (A) contains constituent units derived from other monomers, the content of the constituent units derived from other monomers can be set appropriately within a range that does not impair the effect of the adhesive composition of this disclosure.

[0038] <<Glass transition temperature of (meth)acrylic copolymer (A)>> The glass transition temperature (also called "Tg") of (meth)acrylic copolymer (A) is -45°C to -5°C. When the glass transition temperature of the (meth)acrylic copolymer (A) is -45°C or higher, cohesive failure of the adhesive layer around the protrusions of the adherend tends to be less likely to occur during three-dimensional molding. From this viewpoint, the glass transition temperature of the (meth)acrylic copolymer (A) is preferably -40°C or higher, more preferably -35°C or higher, and even more preferably -30°C or higher. When the glass transition temperature of the (meth)acrylic copolymer (A) is -5°C or lower, the adhesive layer exhibits sufficient wettability to the adherend, and the adhesive strength of the adhesive layer to the adherend tends to be sufficiently high. From this viewpoint, the glass transition temperature of the (meth)acrylic copolymer (A) is preferably -10°C or lower, and more preferably -15°C or lower. The glass transition temperature of the (meth)acrylic copolymer (A) may, in some embodiments, be -40°C to -10°C, -35°C to -10°C, or -30°C to -15°C.

[0039] The glass transition temperature of the (meth)acrylic copolymer (A) is the absolute temperature (unit: K) calculated from Equation 1 below and converted to Celsius temperature (unit: °C). 1 / Tg=m1 / Tg1+m2 / Tg2+ +m(k-1) / Tg(k-1)+mk / Tgk (Formula 1)

[0040] In Equation 1, Tg1, Tg2, ..., Tg(k-1), and Tgk represent the glass transition temperatures expressed in absolute temperature when each monomer constituting the (meth)acrylic copolymer (A) is a homopolymer. m1, m2, ..., m(k-1), and mk represent the mole fractions of each monomer constituting the (meth)acrylic copolymer (A), where m1 + m2 + ... + m(k-1) + mk = 1. Furthermore, absolute temperature can be converted to Celsius temperature by subtracting 273 from it, and Celsius temperature can be converted back to absolute temperature by adding 273 to it.

[0041] In this disclosure, the "glass transition temperature when used as a homopolymer" shall be the value described in publicly available documents or the value measured using a differential scanning calorimetry (DSC). Specifically, the choice of which value to use is as follows:

[0042] For the "glass transition temperatures when the monomers listed below are homopolymers," the values ​​indicated for each monomer should be used. 2-Ethylhexyl acrylate: -70°C, 2-Ethylhexyl methacrylate: -10°C, n-Butyl acrylate: -54°C, n-Butyl methacrylate: 20°C, t-Butyl acrylate: 43°C, t-Butyl methacrylate: 118°C, i-Butyl methacrylate: 53°C, Methyl acrylate: 10°C, Methyl methacrylate: 105°C, Ethyl acrylate: -22°C, Ethyl methacrylate: 65°C, Methacrylic acid: 228°C, 4-Hydroxybutyl acrylate: -80°C, 2-Hydroxyethyl acrylate: -15°C, 2-Hydroxyethyl methacrylate Methacrylate: 85°C, Acrylic acid: 106°C, n-Octyl acrylate: -65°C, Stearyl acrylate: 30°C, Stearyl methacrylate: 38°C, Lauryl acrylate: -3°C, Lauryl methacrylate: -65°C, ω-Carboxypolycaprolactone (n≒2) monoacrylate: -30°C, Phenoxyethyl acrylate: -22°C, Methoxyethyl acrylate: -50°C, Methoxypolyethylene glycol methacrylate: -60°C, 2-Dimethylaminoethyl methacrylate: 18°C, 2-Diethylaminoethyl methacrylate: 20°C.

[0043] For monomers other than those mentioned above, the "glass transition temperature when used as a homopolymer" will be based on the values ​​listed in the Polymer Handbook (4th edition, Wiley-Interscience; hereafter the same). If the value is not listed in the Polymer Handbook, the glass transition temperature of the homopolymer obtained by the following measurement method will be used.

[0044] -Measurement of glass transition temperature of homopolymers- A differential scanning calorimetry (DSC) was used to measure the glass transition temperature of the homopolymer under conditions of a nitrogen atmosphere, with a sample of 10 mg and a heating rate of 10°C / min. The inflection point of the resulting DSC curve was defined as the glass transition temperature of the homopolymer. As a differential scanning calorimetry device, for example, a differential scanning calorimeter (product name: Discovery DSC 2500) manufactured by T.A. Instrument Japan Co., Ltd. can be suitably used. However, the differential scanning calorimetry device is not limited to this.

[0045] The glass transition temperature of the (meth)acrylic copolymer (A) can be appropriately adjusted, for example, by using two or more monomers that have different glass transition temperatures when used as a single polymer.

[0046] <<Weight-average molecular weight of (meth)acrylic copolymer (A)>> The weight-average molecular weight (also called "Mw") of the (meth)acrylic copolymer (A) is not particularly limited, but is preferably 400,000 to 2,500,000, more preferably 500,000 to 2,500,000, and even more preferably 600,000 to 2,500,000. When the weight-average molecular weight of the (meth)acrylic copolymer (A) is 400,000 or more, thermal shrinkage of the adhesive layer due to a decrease in cohesive force tends to be less likely to occur. (Meth)acrylic copolymers (A) tend to be easier to manufacture when their weight-average molecular weight is 2.5 million or less.

[0047] The weight-average molecular weight of (meth)acrylic copolymer (A) is the value measured by the following method. Specifically, it is measured according to (1) to (3) below. (1) A solution of (meth)acrylic copolymer (A) is applied to release paper and dried at 100°C for 1 minute to obtain a film-like (meth)acrylic copolymer (A). (2) Using the film-like (meth)acrylic copolymer (A) obtained in (1) above and tetrahydrofuran, a sample solution with a solid content concentration of 0.2% by mass is obtained. Here, "solid content concentration" refers to the mass ratio of (meth)acrylic copolymer (A) in the sample solution. (3) The weight-average molecular weight of the (meth)acrylic copolymer (A) is determined as a standard polystyrene equivalent by gel permeation chromatography (GPC) under the following conditions.

[0048] ~Conditions~ Measurement device: High-speed GPC [Model number: HLC-8420 GPC, manufactured by Tosoh Corporation] Detector: Differential Refractometer (RI) [Integrated into HLC-8420, manufactured by Tosoh Corporation] Column: TSKgel GMH XL Two units manufactured by Tosoh Corporation were used. Column temperature: 40℃ Eluent: Tetrahydrofuran Sample solution injection volume: 100 μL Flow rate: 0.8mL / min

[0049] The weight-average molecular weight of (meth)acrylic copolymer (A) can be adjusted to a desired value by controlling the polymerization temperature, polymerization time, amount of organic solvent used, type of polymerization initiator, and amount of polymerization initiator used when polymerizing the monomer.

[0050] <<Content of (meth)acrylic copolymer (A)>> The content of the (meth)acrylic copolymer (A) in the adhesive composition of this disclosure is not particularly limited, but is preferably 60% to 97% by mass, more preferably 70% to 96% by mass, and even more preferably 75% to 95% by mass, based on the total solid content in the adhesive composition.

[0051] In this disclosure, "total solid content in the adhesive composition" means the total mass of the adhesive composition if the adhesive composition does not contain a solvent, and the mass of the residue remaining after removing the solvent from the adhesive composition if the adhesive composition contains a solvent. In this disclosure, “solvent” means water and / or an organic solvent.

[0052] [(meth)acrylic copolymer (B)] The adhesive composition of this disclosure comprises a (meth)acrylic copolymer (B). The (meth)acrylic copolymer (B) contains constituent units derived from monomers having at least one amino group selected from the group consisting of primary amino groups, secondary amino groups, and tertiary amino groups, and has a glass transition temperature of 50°C to 100°C. The adhesive composition of this disclosure may contain only one (meth)acrylic copolymer (B), or it may contain two or more.

[0053] <Constituent units derived from monomers containing amino groups> The (meth)acrylic copolymer (B) contains constituent units derived from monomers having at least one amino group selected from the group consisting of primary amino groups, secondary amino groups, and tertiary amino groups. In this disclosure, "constituent unit derived from a monomer having an amino group" means a constituent unit formed by the addition polymerization of a monomer having an amino group.

[0054] The type of monomer having an amino group is not particularly limited. Examples of monomers having an amino group include monomers having at least one amino group and an ethylenically unsaturated group in one molecule. The ethylenically unsaturated group is not particularly limited and includes, for example, a vinyl group, an allyl group, a vinylphenyl group, a (meth)acrylamide group, and a (meth)acryloyl group. A (meth)acryloyl group is preferred as the ethylenically unsaturated group.

[0055] Specific examples of monomers having an amino group include 2-dimethylaminoethyl (meth)acrylate, 2-diethylaminoethyl (meth)acrylate, 2-diisopropylaminoethyl (meth)acrylate, and dimethylaminopropyl (meth)acrylamide. As the monomer having an amino group, (meth)acrylic monomers having an amino group are preferred, alkyl (meth)acrylate esters having an amino group are more preferred, at least one selected from the group consisting of 2-dimethylaminoethyl (meth)acrylate and 2-diethylaminoethyl (meth)acrylate is even more preferred, and at least one selected from 2-dimethylaminoethyl methacrylate and 2-diethylaminoethyl methacrylate is particularly preferred.

[0056] The (meth)acrylic copolymer (B) may contain only one or more constituent units derived from monomers having an amino group.

[0057] The total content of constituent units derived from monomers having amino groups in (meth)acrylic copolymer (B) is not particularly limited, but for example, from the viewpoint of compatibility between (meth)acrylic copolymer (A) and (meth)acrylic copolymer (B), it is preferably 1.5% by mass or more, more preferably 2% by mass or more, even more preferably 2.5% by mass or more, and particularly preferably 3% by mass or more, relative to the total constituent units of (meth)acrylic copolymer (B). The upper limit of the total content of constituent units derived from monomers having amino groups in the (meth)acrylic copolymer (B) may be, for example, 20% by mass or less, 15% by mass or less, 12% by mass or less, 10% by mass or less, or 6% by mass or less, relative to the total constituent units of the (meth)acrylic copolymer (B). In some embodiments, the total content of constituent units derived from monomers having amino groups in the (meth)acrylic copolymer (B) may be 1.5% to 20% by mass, 2% to 15% by mass, 2.5% to 12% by mass, 3% to 10% by mass, or 3% to 6% by mass, relative to the total constituent units of the (meth)acrylic copolymer (B).

[0058] <Constituent units derived from alkyl methacrylate monomers> The (meth)acrylic copolymer (B) preferably contains constituent units derived from an alkyl (meth)acrylate monomer that does not have an amino group. Furthermore, the term "(meth)acrylic acid alkyl ester monomer" in (meth)acrylic copolymer (B) does not include monomers that have an amino group. In other words, if a monomer having an amino group also falls under the category of (meth)acrylic acid alkyl ester monomer, it will be classified as a monomer having an amino group.

[0059] The type of alkyl (meth)acrylate monomer is not particularly limited. The alkyl (meth)acrylate monomer may be an alkyl acrylate monomer or an alkyl methacrylate monomer. The alkyl group in the alkyl (meth)acrylate monomer may be unsubstituted or substituted, but it is preferable that it be unsubstituted. The alkyl group of the alkyl (meth)acrylate monomer may be linear, branched, or cyclic. The number of carbon atoms in the alkyl group of the (meth)acrylate monomer is preferably 1 to 18, more preferably 1 to 12, even more preferably 1 to 8, and particularly preferably 1 to 4.

[0060] Specific examples of alkyl (meth)acrylate monomers are the same as those described in (meth)acrylic copolymer (A), so their explanation is omitted here. The alkyl (meth)acrylate monomer preferably contains at least one of methyl methacrylate and ethyl acrylate, and more preferably contains both methyl methacrylate and ethyl acrylate.

[0061] The (meth)acrylic copolymer (B) may contain constituent units derived from alkyl (meth)acrylate monomers, and may contain only one or two or more such constituent units.

[0062] When the (meth)acrylic copolymer (B) contains structural units derived from alkyl (meth)acrylate monomers, the content of structural units derived from alkyl (meth)acrylate monomers is not particularly limited, but for example, it is preferably 50% by mass or more, more preferably 50% to 98.5% by mass, even more preferably 60% to 98% by mass, and particularly preferably 70% to 97% by mass, relative to the total structural units of the (meth)acrylic copolymer (B). Here, the content of constituent units derived from alkyl methacrylate monomers in (meth)acrylic copolymer (B) being 50% by mass or more of the total constituent units of (meth)acrylic copolymer (B) means that constituent units derived from alkyl methacrylate monomers are included as the main component of the constituent units of (meth)acrylic copolymer (B).

[0063] <Constituent units derived from other monomers> The (meth)acrylic copolymer (B) may contain constituent units derived from monomers that do not fall under either monomers having an amino group or alkyl (meth)acrylate monomers (so-called other monomers).

[0064] Specific examples of constituent units derived from other monomers are the same as those described in the section on (meth)acrylic copolymer (A), so their explanation is omitted here.

[0065] If the (meth)acrylic copolymer (B) contains constituent units derived from other monomers, it may contain only one type of constituent unit derived from other monomers, or it may contain two or more types.

[0066] If the (meth)acrylic copolymer (B) contains constituent units derived from other monomers, the content of the constituent units derived from other monomers can be appropriately set within a range that does not impair the effect of the adhesive composition of this disclosure.

[0067] <<Glass transition temperature of (meth)acrylic copolymer (B)>> The glass transition temperature (Tg) of (meth)acrylic copolymer (B) is 50°C to 100°C. When the glass transition temperature of the (meth)acrylic copolymer (B) is 50°C or higher, cohesive failure of the adhesive layer around the protrusions of the adherend tends to be less likely to occur during three-dimensional molding. From this viewpoint, the glass transition temperature of the (meth)acrylic copolymer (B) is preferably 60°C or higher, and more preferably 70°C or higher. The glass transition temperature of the (meth)acrylic copolymer (B) is preferably 100°C or lower, and more preferably 95°C or lower, from the viewpoint of suitability for manufacturing. The glass transition temperature of the (meth)acrylic copolymer (B) may, in some embodiments, be 60°C to 100°C, 70°C to 100°C, 60°C to 95°C, or 70°C to 95°C.

[0068] The glass transition temperature of (meth)acrylic copolymer (B) is a value that can be determined by the same method as the method for determining the glass transition temperature of (meth)acrylic copolymer (A) described above.

[0069] The glass transition temperature of the (meth)acrylic copolymer (B) can be appropriately adjusted, for example, by using two or more monomers that have different glass transition temperatures when used as homopolymers.

[0070] <<Weight-average molecular weight of (meth)acrylic copolymer (B)>> The weight-average molecular weight (Mw) of the (meth)acrylic copolymer (B) is not particularly limited, but is preferably 0.5 million to 200,000, more preferably 10,000 to 200,000, and even more preferably 50,000 to 150,000. When the weight-average molecular weight of (meth)acrylic copolymer (B) is 0.5 million or more, it tends to exhibit appropriate cohesive force because it is moderately compatible with (meth)acrylic copolymer (A). (Meth)acrylic copolymers (B) with a weight-average molecular weight of 200,000 or less tend to be easier to manufacture.

[0071] The weight-average molecular weight of (meth)acrylic copolymer (B) is a value measured by the same method as the method for measuring the weight-average molecular weight of (meth)acrylic copolymer (A) described above.

[0072] The weight-average molecular weight of (meth)acrylic copolymer (B) can be adjusted to a desired value by controlling the polymerization temperature, polymerization time, amount of organic solvent used, type of polymerization initiator, and amount of polymerization initiator used when polymerizing the monomers.

[0073] <<Content of (meth)acrylic copolymer (B)>> The content of the (meth)acrylic copolymer (B) in the adhesive composition of this disclosure is 5 to 25 parts by mass per 100 parts by mass of the (meth)acrylic copolymer (A) described above. In the adhesive composition of this disclosure, if the content of (meth)acrylic copolymer (B) is 5 parts by mass or more per 100 parts by mass of (meth)acrylic copolymer (A), the cohesive force of the adhesive layer is sufficiently increased, and cohesive failure of the adhesive layer around the convex parts of the adherend tends to be less likely to occur during three-dimensional molding. From this viewpoint, the content of (meth)acrylic copolymer (B) in the adhesive composition of this disclosure is preferably 8 parts by mass or more, and more preferably 10 parts by mass or more, per 100 parts by mass of (meth)acrylic copolymer (A). In the adhesive composition of this disclosure, if the content of (meth)acrylic copolymer (B) is 25 parts by mass or less per 100 parts by mass of (meth)acrylic copolymer (A), the cohesive force of the adhesive layer does not become excessively high, and the decrease in the adhesive strength of the adhesive layer to the adherend tends to be suppressed. From this viewpoint, the content of (meth)acrylic copolymer (B) in the adhesive composition of this disclosure is preferably 23 parts by mass or less, and more preferably 20 parts by mass or less, per 100 parts by mass of (meth)acrylic copolymer (A). In some embodiments, the content of the (meth)acrylic copolymer (B) in the adhesive composition of the present disclosure may be 5 to 23 parts by mass, 5 to 20 parts by mass, 8 to 23 parts by mass, or 10 to 20 parts by mass per 100 parts by mass of the (meth)acrylic copolymer (A).

[0074] [Meth)acrylic copolymer manufacturing method] The method for producing (meth)acrylic copolymer (A) and (meth)acrylic copolymer (B) [i.e., a specific (meth)acrylic copolymer] is not particularly limited. Specific (meth)acrylic copolymers can be produced by polymerizing the monomers described above using known polymerization methods, such as solution polymerization, emulsion polymerization, suspension polymerization, and bulk polymerization. As for the polymerization method, solution polymerization is preferred because the processing steps for preparing the adhesive composition of this disclosure after manufacturing are relatively simple and can be carried out in a short time.

[0075] In solution polymerization, a predetermined organic solvent, monomer, polymerization initiator, and a chain transfer agent (if necessary) are generally placed in a polymerization tank, and the reaction is carried out by heating for several hours at the reflux temperature of the organic solvent while stirring. In this case, at least a portion of the organic solvent, monomer, polymerization initiator, and chain transfer agent (if necessary) may be added sequentially. Alternatively, the reaction may be carried out under a nitrogen atmosphere.

[0076] Examples of organic solvents used in polymerization reactions include aromatic hydrocarbon compounds, aliphatic hydrocarbon compounds, alicyclic hydrocarbon compounds, ester compounds, ketone compounds, glycol ether compounds, and alcohol compounds. More specifically, organic solvents used in polymerization reactions include aromatic hydrocarbon compounds such as benzene, toluene, ethylbenzene, n-propylbenzene, t-butylbenzene, o-xylene, m-xylene, p-xylene, tetralin, decalin, and aromatic naphtha; aliphatic or alicyclic hydrocarbon compounds such as n-hexane, n-heptane, n-octane, i-octane, n-decane, dipentene, petroleum spirits, petroleum naphtha, and turpentine oil; ester compounds such as methyl acetate, ethyl acetate, n-butyl acetate, n-amyl acetate, 2-hydroxyethyl acetate, 2-butoxyethyl acetate, 3-methoxybutyl acetate, and methyl benzoate; acetone; and methyl Examples include ketone compounds represented by ethyl ketone, methyl-i-butyl ketone, isophorone, cyclohexanone, and methylcyclohexanone; glycol ether compounds represented by ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, and diethylene glycol monobutyl ether; and alcohol compounds represented by methyl alcohol, ethyl alcohol, n-propyl alcohol, i-propyl alcohol, n-butyl alcohol, i-butyl alcohol, s-butyl alcohol, and t-butyl alcohol.

[0077] In the production of specific (meth)acrylic copolymers, it is preferable to use organic solvents that do not easily cause chain transfer during polymerization reactions, such as aromatic hydrocarbon compounds, ester compounds, and ketone compounds. In particular, from the viewpoint of solubility of the specific (meth)acrylic copolymer and ease of polymerization reaction, the use of methyl acetate and / or ethyl acetate is preferred.

[0078] During the polymerization reaction, one organic solvent may be used, or two or more may be used.

[0079] Examples of polymerization initiators include organic peroxides and azo compounds commonly used in conventional solution polymerization methods. Specific examples of organic peroxides include t-butylperoxy-2-ethylhexanoate, t-butylhydroperoxide, cumenehydroperoxide, dicumylperoxide, benzoylperoxide, lauroylperoxide, caproylperoxide, di-i-propylperoxydicarbonate, di-2-ethylhexylperoxydicarbonate, t-butylperoxypivalate, and 2,2-bis(4,4-di-t-butylperoxy). Examples include chlorohexyl)propane, 2,2-bis(4,4-di-t-amylperoxycyclohexyl)propane, 2,2-bis(4,4-di-t-octylperoxycyclohexyl)propane, 2,2-bis(4,4-di-α-cumylperoxycyclohexyl)propane, 2,2-bis(4,4-di-t-butylperoxycyclohexyl)butane, and 2,2-bis(4,4-di-t-octylperoxycyclohexyl)butane. Specific examples of azo compounds include 2,2'-azobisisobutyronitrile [AIBN], 2,2'-azobis(2,4-dimethylvaleronitrile) [ABVN], 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 1,1'-azobis(cyclohexane-1-carbonitride), and 2,2'-azobis(isobutyric acid)dimethyl.

[0080] During the polymerization reaction, one polymerization initiator may be used, or two or more may be used.

[0081] The amount of polymerization initiator used is not particularly limited and can be appropriately set, for example, depending on the molecular weight of the target specific (meth)acrylic copolymer.

[0082] In the production of specific (meth)acrylic copolymers, chain transfer agents may be used as needed. Examples of chain transfer agents include cyanoacetic acid, alkyl ester compounds of cyanoacetic acid with 1 to 8 carbon atoms, bromoacetic acid, alkyl ester compounds of bromoacetic acid with 1 to 8 carbon atoms, aromatic compounds represented by α-methylstyrene, anthracene, phenanthrene, fluorene, and 9-phenylfluorene, aromatic nitro compounds represented by p-nitroaniline, nitrobenzene, dinitrobenzene, p-nitrobenzoic acid, p-nitrophenol, and p-nitrotoluene, benzoquinone derivatives represented by benzoquinone and 2,3,5,6-tetramethyl-p-benzoquinone, borane derivatives represented by tributylborane, carbon tetrabromide, and tetra- Examples include halogenated hydrocarbon compounds represented by carbon chloride, 1,1,2,2-tetrabromoethane, tribromoethylene, trichloroethylene, bromotrichloromethane, tribromomethane, and 3-chloro-1-propene; aldehyde compounds represented by chloral and furaldihydes; alkyl mercaptan compounds having 1 to 18 carbon atoms; aromatic mercaptan compounds represented by thiophenol and toluene mercaptan; mercaptoacetic acid; alkyl ester compounds of mercaptoacetic acid having 1 to 10 carbon atoms; hydroxyalkyl mercaptan compounds having 1 to 12 carbon atoms; and terpene compounds represented by pinene and terpinolene.

[0083] When using a chain transfer agent in the production of a specific (meth)acrylic copolymer, the amount of the chain transfer agent used is not particularly limited and can be appropriately set, for example, depending on the molecular weight of the target specific (meth)acrylic copolymer.

[0084] The polymerization temperature is not particularly limited and can be set appropriately depending on the molecular weight of the target specific (meth)acrylic copolymer.

[0085] [Crosslinking agent] The adhesive composition of this disclosure includes an epoxy-based crosslinking agent or an isocyanate-based crosslinking agent as a crosslinking agent. The following describes epoxy-based crosslinking agents and isocyanate-based crosslinking agents.

[0086] [Epoxy-based crosslinking agent] The first adhesive composition of this disclosure comprises an epoxy crosslinking agent. The first adhesive composition of this disclosure may contain only one epoxy crosslinking agent or may contain two or more epoxy crosslinking agents. In this disclosure, "epoxy crosslinking agent" refers to a compound having two or more epoxy groups in one molecule (a so-called bifunctional or multifunctional epoxy compound). Examples of bifunctional or more epoxy compounds include ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, polytetramethylene glycol diglycidyl ether, glycerol diglycidyl ether, glycerol triglycidyl ether, and diglycerol polyglycidyl ether. Examples include tel, polyglycerol polyglycidyl ether, resorcinol diglycidyl ether, 2,2-dibromoneopentyl glycol diglycidyl ether, trimethylolpropane triglycidyl ether, pentaerythritol polyglycidyl ether, sorbitol polyglycidyl ether, diglycidyl adipate ester, diglycidyl phthalate ester, tris(glycidyl) isocyanurate, tris(glycidoxyethyl) isocyanurate, 1,3-bis(N,N-glycidylaminomethyl)cyclohexane, and N,N,N',N'-tetraglycidyl-m-xylylenediamine. As the epoxy crosslinking agent, 1,3-bis(N,N-glycidylaminomethyl)cyclohexane or N,N,N',N'-tetraglycidyl-m-xylylenediamine are preferred.

[0087] Commercially available epoxy crosslinking agents can be used. Examples of commercially available epoxy crosslinking agents include "TETRAD(registered trademark)-X" and "TETRAD(registered trademark)-C" (both manufactured by Mitsubishi Gas Chemical Company, Inc.), and "Denacol(registered trademark) EX-201" and "Denacol(registered trademark) EX-931" (both manufactured by Nagase ChemteX Corporation).

[0088] <<Ratio of the number of moles of epoxy groups in the epoxy crosslinking agent to the number of moles of carboxyl groups in the (meth)acrylic copolymer (A)>> In the first adhesive composition of this disclosure, the ratio of the number of moles of epoxy groups in the epoxy crosslinking agent to the number of moles of carboxyl groups in the (meth)acrylic copolymer (A) is 0.0045 or more. When the ratio of the number of moles of epoxy groups in the epoxy crosslinking agent to the number of moles of carboxyl groups in the (meth)acrylic copolymer (A) is 0.0045 or more, the cohesive force of the adhesive layer is sufficiently increased, so that cohesive failure of the adhesive layer is less likely to occur around the protrusions of the adherend during three-dimensional molding. On the other hand, the ratio of the number of moles of epoxy groups in the epoxy crosslinking agent to the number of moles of carboxyl groups in the (meth)acrylic copolymer (A) is preferably 0.5 or less from the viewpoint of suppressing peeling around the protrusions of the adherend during three-dimensional molding. The ratio of moles of epoxy groups in the epoxy crosslinking agent to moles of carboxyl groups in the (meth)acrylic copolymer (A) is preferably 0.006 or higher, more preferably 0.007 or higher, and even more preferably 0.008 or higher. The ratio of moles of epoxy groups in the epoxy crosslinking agent to moles of carboxyl groups in the (meth)acrylic copolymer (A) is preferably 0.5 or lower, more preferably 0.3 or lower, and even more preferably 0.1 or lower. The ratio of moles of epoxy groups in the epoxy crosslinking agent to moles of carboxyl groups in the (meth)acrylic copolymer (A) is preferably 0.0045 to 0.5, more preferably 0.007 to 0.3, and even more preferably 0.008 to 0.1.

[0089] The ratio of the number of moles of epoxy groups in the epoxy crosslinking agent to the number of moles of carboxyl groups in the (meth)acrylic copolymer (A) can be calculated using the following formulas (1) to (3). (1) "Number of moles of reactive functional groups (epoxy groups) in epoxy crosslinking agent [unit: mmol] = Amount of epoxy crosslinking agent [amount as solid content] (unit: g)] / Epoxy equivalent (g / eq) × 1000" (2) "The number of moles of carboxyl groups in (meth)acrylic copolymer (A) [unit: mmol] = [Content of constituent units derived from monomers having carboxyl groups in (meth)acrylic copolymer (A) (unit: mass%) / 100 × Amount of (meth)acrylic copolymer (A) blended (unit: g) / Molecular weight of constituent units derived from monomers having carboxyl groups (unit: g / mol) × Number of carboxyl groups (valence) in constituent units derived from monomers having carboxyl groups × 1000" (3) "Ratio of the number of moles of reactive functional groups in the epoxy crosslinking agent to the number of moles of carboxyl groups in the (meth)acrylic copolymer (A) = Value obtained by formula (1) / Value obtained by formula (2)" In this disclosure, the epoxy equivalent (molecular weight / number of epoxy groups, unit: g / eq) is a value measured according to the method in accordance with JIS K 7236:2009. When using commercially available resins containing epoxy groups, the epoxy equivalent of the resin shall be based on the catalog value of the commercially available product.

[0090] The content of the epoxy crosslinking agent in the first adhesive composition of this disclosure is not particularly limited as long as the ratio of the number of moles of epoxy groups in the epoxy crosslinking agent to the number of moles of carboxyl groups in the (meth)acrylic copolymer (A) is 0.0045 or more. For example, it is preferably 0.03 to 3 parts by mass, more preferably 0.035 to 2 parts by mass, and even more preferably 0.04 to 0.6 parts by mass per 100 parts by mass of the (meth)acrylic copolymer (A). When the content of the epoxy crosslinking agent in the first adhesive composition of this disclosure is within the above range relative to 100 parts by mass of (meth)acrylic copolymer (A), an adhesive layer can be formed that has high adhesive strength to the adherend and is less likely to cause appearance defects during three-dimensional molding.

[0091] [Isocyanate-based crosslinking agents] The second adhesive composition of this disclosure comprises an isocyanate crosslinking agent. The second adhesive composition of this disclosure may contain only one isocyanate crosslinking agent or two or more isocyanate crosslinking agents. In this disclosure, "isocyanate-based crosslinking agent" refers to a compound having two or more isocyanate groups in one molecule (a so-called polyisocyanate compound).

[0092] Examples of polyisocyanate compounds include aliphatic polyisocyanate compounds, alicyclic polyisocyanate compounds, and aromatic polyisocyanate compounds.

[0093] "Aliphatic polyisocyanate compounds" include, for example, aliphatic polyisocyanate compounds, polymers of aliphatic polyisocyanate compounds, adduct compounds of aliphatic polyisocyanate compounds and polyol compounds [e.g., trimethylolpropane (TMP); the same applies hereinafter], and biuret compounds of aliphatic polyisocyanate compounds. Specific examples of aliphatic polyisocyanate compounds include hexamethylene diisocyanate (HMDI), pentamethylene diisocyanate (PDI), tetramethylene diisocyanate, trimethylhexamethylene diisocyanate, and lysine diisocyanate.

[0094] "Alicyclic polyisocyanate compounds" include, for example, alicyclic polyisocyanate compounds, polymers of alicyclic polyisocyanate compounds, adducts of alicyclic polyisocyanate compounds and polyol compounds, and biuret compounds of alicyclic polyisocyanate compounds. Specific examples of alicyclic polyisocyanate compounds include isophorone diisocyanate (IPDI), hydrogenated tolylene diisocyanate, hydrogenated xylylene diisocyanate, hydrogenated 4,4'-diphenylmethane diisocyanate, and 4,4'-dicyclohexylmethane diisocyanate.

[0095] "Aromatic polyisocyanate compounds" include, for example, aromatic polyisocyanate compounds, polymers of aromatic polyisocyanate compounds, adduct compounds of aromatic polyisocyanate compounds and polyol compounds, and biuret compounds of aromatic polyisocyanate compounds. Specific examples of aromatic polyisocyanate compounds include tolylene diisocyanate (TDI), xylylene diisocyanate (XDI), and 4,4'-diphenylmethane diisocyanate.

[0096] As for the polyisocyanate compound, an adduct of IPDI and TMP or an adduct of HMDI and TMP is preferred.

[0097] Commercially available isocyanate-based crosslinking agents can be used. Examples of commercially available isocyanate-based crosslinking agents include "Coronate® HX", "Coronate® HL-S", "Coronate® L", "Coronate® L-45E", "Coronate® 2031", "Coronate® 2037", "Coronate® 2234", "Coronate® 2785", "Aquanate® 200", and "Aquanate® 210" [all manufactured by Tosoh Corporation], "Sumijoule® N3300", "Desmodule® N3400", and "Sumijoule® N75" [all manufactured by Sumika Covestro Urethane Co., Ltd.], "Duranate® D201", "Duranate® E405-70B", "Duranate® E405-80T", and "Duranate® Examples include "AE700-100", "Duranate® 24A-100", and "Duranate® TSE-100" (all manufactured by Asahi Kasei Corporation), as well as "Takenate® D-110N", "Takenate® D-101E", "Takenate® D-120N", "Takenate® D-140N", "Takenate® M-631N", "MT-Orestar® NP1200", and "Stavio® XD-340N" (all manufactured by Mitsui Chemicals, Inc.).

[0098] <<Ratio of the number of moles of isocyanate groups in the isocyanate crosslinking agent to the number of moles of carboxyl groups in the (meth)acrylic copolymer (A)>> In the second adhesive composition of this disclosure, the ratio of the number of moles of isocyanate groups in the isocyanate crosslinking agent to the number of moles of carboxyl groups in the (meth)acrylic copolymer (A) is 0.1 to 0.5. When the ratio of the number of moles of isocyanate groups in the isocyanate crosslinking agent to the number of moles of carboxyl groups in the (meth)acrylic copolymer (A) is 0.1 or higher, the cohesive force of the adhesive layer is sufficiently increased, making it less likely for cohesive failure of the adhesive layer to occur around the convex parts of the adherend during three-dimensional molding. On the other hand, when the ratio of the number of moles of isocyanate groups in the isocyanate crosslinking agent to the number of moles of carboxyl groups in the (meth)acrylic copolymer (A) is 0.5 or lower, the cohesive force of the adhesive layer does not become excessively high, and the decrease in the adhesive strength of the adhesive layer to the adherend tends to be suppressed. The ratio of the number of moles of isocyanate groups in the isocyanate crosslinking agent to the number of moles of carboxyl groups in the (meth)acrylic copolymer (A) is preferably 0.1 or higher, more preferably 0.15 or higher, and even more preferably 0.18 or higher. The ratio of the number of moles of isocyanate groups in the isocyanate crosslinking agent to the number of moles of carboxyl groups in the (meth)acrylic copolymer (A) is preferably 0.5 or lower, more preferably 0.45 or lower, and even more preferably 0.4 or lower. The ratio of the number of moles of isocyanate groups in the isocyanate crosslinking agent to the number of moles of carboxyl groups in the (meth)acrylic copolymer (A) is preferably 0.15 to 0.45, and even more preferably 0.18 to 0.4.

[0099] The ratio of the number of moles of isocyanate groups in the isocyanate crosslinking agent to the number of moles of carboxyl groups in the (meth)acrylic copolymer (A) can be calculated using the following formulas (1) to (3). (1) "Number of moles of reactive functional groups (isocyanate groups) in isocyanate crosslinking agents [unit: mmol] = [Isocyanate group content in isocyanate crosslinking agent (unit: mass%) / Solid content concentration of isocyanate crosslinking agent (unit: mass%) × Amount of isocyanate crosslinking agent [amount as solid content] (unit: g)] / Molecular weight of isocyanate group (unit: g / mol) × 1000" (2) "The number of moles of carboxyl groups in (meth)acrylic copolymer (A) [unit: mmol] = [Content of constituent units derived from monomers having carboxyl groups in (meth)acrylic copolymer (A) (unit: mass%) / 100 × Amount of (meth)acrylic copolymer (A) blended (unit: g) / Molecular weight of constituent units derived from monomers having carboxyl groups (unit: g / mol) × Number of carboxyl groups (valence) in constituent units derived from monomers having carboxyl groups × 1000" (3) "Ratio of the number of moles of reactive functional groups in the isocyanate crosslinking agent to the number of moles of carboxyl groups in the (meth)acrylic copolymer (A) = Value obtained by formula (1) / Value obtained by formula (2)"

[0100] The content of the isocyanate crosslinking agent in the second adhesive composition of this disclosure is not particularly limited as long as the ratio of the number of moles of isocyanate groups in the isocyanate crosslinking agent to the number of moles of carboxyl groups in the (meth)acrylic copolymer (A) is 0.1 to 0.5. For example, it is preferably 0.5 to 15 parts by mass, more preferably 1.5 to 8.5 parts by mass, even more preferably 2.5 to 7.5 parts by mass, and particularly preferably 3 to 7 parts by mass per 100 parts by mass of the (meth)acrylic copolymer (A). When the content of the isocyanate-based crosslinking agent in the second adhesive composition of this disclosure is within the above range relative to 100 parts by mass of (meth)acrylic copolymer (A), an adhesive layer can be formed that has high adhesive strength to the adherend and is less likely to cause appearance defects during three-dimensional molding.

[0101] In this disclosure, the first and second adhesive compositions may contain other crosslinking agents as long as they do not impair the effects. For example, the first adhesive composition may contain an isocyanate-based crosslinking agent, and the second adhesive composition may contain an epoxy-based crosslinking agent. Furthermore, the first and second adhesive compositions may contain other known crosslinking agents such as metal chelate-based crosslinking agents or aziridine-based crosslinking agents.

[0102] [Organic solvents] The adhesive composition of this disclosure may contain an organic solvent. The adhesive composition of this disclosure may have improved applicability and pot life when it contains an organic solvent. Examples of organic solvents include those similar to those used in the polymerization reaction of the specific (meth)acrylic copolymers described above.

[0103] If the adhesive composition of this disclosure contains an organic solvent, it may contain only one organic solvent or two or more organic solvents.

[0104] If the adhesive composition of this disclosure contains an organic solvent, the content of the organic solvent is not particularly limited and can be set as appropriate depending on the purpose.

[0105] [Other ingredients] The adhesive composition of this disclosure may, if necessary, contain components other than those described above (so-called other components), as long as they do not impair its effect. Other components include polymers other than (meth)acrylic copolymer (A) and (meth)acrylic copolymer (B), crosslinking catalysts, antioxidants, light stabilizers (e.g., UV absorbers), and various other additives.

[0106] If the adhesive composition of this disclosure contains other components, the content of these other components can be set as appropriate, as long as it does not impair the effects of the adhesive composition of this disclosure.

[0107] [Overlaminate film] The overlaminate film of this disclosure comprises a surface protective film and an adhesive layer provided on one side of the surface protective film and formed of the adhesive composition of this disclosure. The overlaminate film of this disclosure comprises an adhesive layer formed by the adhesive composition of this disclosure, and therefore has high adhesive strength to the adherend and is less likely to cause appearance defects during three-dimensional molding.

[0108] The material of the substrate to which the overlaminate film of this disclosure is deposited is not particularly limited, and examples include resins (e.g., polyurethane resins) and metals (e.g., aluminum plates).

[0109] The material of the surface protective film is not particularly limited. Examples of surface protective films include films containing resins such as polyolefin resins (e.g., polyethylene (PE) and polypropylene (PP)), polyester resins (e.g., polyethylene terephthalate (PET)), acetate resins (e.g., triacetylcellulose), polyethersulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyurethane resins, (meth)acrylic resins, vinyl chloride resins, ABS (Acrylonitrile Butadiene Styrene) resins, and fluororesins. The surface protective film is preferably a film containing a polyurethane resin, for example, from the viewpoint of being able to suppress distortion of the molded part that may occur during three-dimensional molding.

[0110] The surface protective film may be colorless or colored, but it is preferable that it be colorless from the viewpoint of not interfering with the design of the decoration applied to the adherend. Furthermore, the surface protective film may be transparent or semi-transparent, but it is preferable that it be transparent so as not to obstruct the visibility of the decoration applied to the adherend. In this disclosure, "transparent" means that the average transmittance of visible light with wavelengths of 400 nm to 700 nm is 80% or more, and preferably 90% or more. In this disclosure, "transmittance" is a value measured using a spectrophotometer.

[0111] The side of the surface protective film on which the adhesive layer is provided may be subjected to surface treatments such as corona discharge treatment or plasma discharge treatment (so-called easy-adhesion treatments) from the viewpoint of improving the adhesion between the surface protective film and the adhesive layer.

[0112] The surface protective film may contain various additives such as crosslinking agents, crosslinking catalysts, plasticizers, heat stabilizers, UV absorbers, light stabilizers, antistatic agents, flame retardants, antioxidants, fillers, defoamers, and surfactants.

[0113] The thickness of the surface protective film is not particularly limited, but is preferably 20 μm to 100 μm, more preferably 25 μm to 90 μm, and even more preferably 30 μm to 80 μm.

[0114] In this disclosure, "thickness of the surface protective film" refers to the average thickness of the surface protective film. The average thickness of the surface protective film is determined by the following method. The thickness of the surface protective film is measured at five randomly selected points along its thickness direction using a constant-pressure thickness gauge (probe diameter: 5 mm). The arithmetic mean of the measured values ​​is calculated, and this value is taken as the average thickness of the surface protective film.

[0115] The surface protective film may be a single layer or may be formed from multiple layers. When a surface protective film is formed from multiple layers, the thickness of the surface protective film as described above refers to the total thickness of the multiple layers that make up the surface protective film.

[0116] The adhesive layer of the overlaminate film of this disclosure is an adhesive layer formed of the adhesive composition of this disclosure and is provided on one side of the surface protective film. Since the adhesive layer of the overlaminate film of this disclosure is formed of the adhesive composition of this disclosure described above, it has high adhesive strength to the adherend and is less likely to cause appearance defects during three-dimensional molding. The adhesive layer is preferably a layer made of the adhesive composition of the present disclosure, or a layer made of the solids of the adhesive composition of the present disclosure.

[0117] The thickness of the adhesive layer is not particularly limited, but is preferably 3 μm to 40 μm, more preferably 5 μm to 35 μm, even more preferably 8 μm to 30 μm, and particularly preferably 10 μm to 25 μm. When the thickness of the adhesive layer is 3 μm or more, the adhesive strength of the adhesive layer to the adherend tends to be more sufficiently high. When the thickness of the adhesive layer is 40 μm or less, cohesive failure of the adhesive layer tends to be less likely to occur around the protrusions of the adherend during three-dimensional molding.

[0118] In this disclosure, "thickness of the adhesive layer" refers to the average thickness of the adhesive layer. The average thickness of the adhesive layer is determined by the following method. The thickness of the adhesive layer is measured at five randomly selected locations in the thickness direction using a constant-pressure thickness gauge (probe diameter: 5 mm). The arithmetic mean of the measured values ​​is calculated, and this value is taken as the average thickness of the adhesive layer.

[0119] In the overlaminate film of this disclosure, the exposed adhesive layer surface may be protected by a release sheet. Generally, the release sheet protects the surface of the adhesive layer until the overlaminate film is put into practical use and is peeled off at the time of use.

[0120] The release sheet is not particularly limited as long as it can be easily peeled off from the adhesive layer. Examples of release sheets include resin films, paper, synthetic paper, and composite sheets made by laminating two or more of these materials, all of which have been surface-treated with a release agent on one or both sides (so-called easy-peel treatment). In this disclosure, a release sheet in which one or both sides of a resin film are subjected to a surface treatment with a release agent (so-called easy-release treatment) is also referred to as a "release film." Examples of release agents include silicone-based release agents (e.g., silicone), wax-based release agents (e.g., paraffin wax), and fluorine-based release agents (e.g., fluorine-based resins). Examples of resin films include polyester films, such as polyethylene terephthalate (PET) film. Examples of paper include high-quality paper and coated paper. The film thickness of the release sheet is not particularly limited, but is generally between 20 μm and 180 μm.

[0121] Figure 1 is a schematic cross-sectional view showing an example of the configuration of the overlaminate film of this disclosure. The overlaminate film 10 shown in Figure 1 comprises a surface protection film 20 and an adhesive layer 30 provided on one side of the surface protection film 20. Details of the surface protection film 20 and the adhesive layer 30 are as previously described.

[0122] The overlaminate film of this disclosure may optionally include layers other than the surface protective film and adhesive layer (also referred to as "other layers"). Other layers include, for example, decorative layers provided on and / or between the surface protective film and the adhesive layer. In this case, the decorative layer is provided to give the overlaminate film a design, and is a layer that expresses patterns, characters, images, etc. The decorative layer can be formed by known printing methods such as inkjet printing, screen printing, gravure printing, hot stamping printing, and baked printing. When the overlaminate film of this disclosure is used for a license plate as described later, a decorative layer is provided on the surface protective film, on which characters (numbers, kanji, hiragana, alphabet, etc.) are formed. The above characters can be formed by, for example, baked printing.

[0123] The overlaminate film of this disclosure has an adhesive layer formed by the adhesive composition of this disclosure, that is, an adhesive layer that has high adhesive strength to the adherend and is less likely to cause appearance defects during three-dimensional molding, and therefore can be suitably used not only for planar articles but also for three-dimensional articles. The overlaminate film of this disclosure can be used, for example, as a component of the license plate of this disclosure as described later. The overlaminate film of this disclosure can also be applied to the interior or exterior of vehicles such as automobiles, and to the interior of buildings such as walls, floors, and ceilings.

[0124] [How to make overlaminate film] The method for producing the overlaminate film described herein is not particularly limited. The overlaminate film of this disclosure can be prepared by known methods using the adhesive composition of this disclosure. Examples of methods for preparing the overlaminate film of this disclosure include the following:

[0125] The adhesive composition of this disclosure is applied to the easily adhesive treated surface of a base film that will serve as a surface protective film, thereby forming a coating film on the base film. Next, the formed coating film is dried to form an adhesive layer on the base film. Then, the exposed surface of the formed adhesive layer is laminated onto the easily peeled surface of a release sheet, and after curing, an overlaminate film of this disclosure having a laminated structure of base film (so-called surface protective film) / adhesive layer / release sheet can be produced.

[0126] Another method, for example, is as follows: The adhesive composition of the present disclosure is applied to the easily peelable surface of a release sheet to form a coating film on the release sheet. Then, the formed coating film is dried to form an adhesive layer on the release sheet. Next, the exposed surface of the formed adhesive layer is laminated onto the easily adhesive surface of a base film that will serve as a surface protective film, and then cured to produce the overlaminate film of the present disclosure having a laminated structure of base film (so-called surface protective film) / adhesive layer / release sheet.

[0127] The method of applying the adhesive composition is not particularly limited. Examples of known methods for applying adhesive compositions include gravure roll coaters, reverse roll coaters, kiss roll coaters, dip roll coaters, knife coaters, spray coaters, bar coaters, applicators, and the like. The amount of adhesive composition applied is not particularly limited and can be appropriately set, for example, depending on the thickness of the adhesive layer to be formed.

[0128] The method for drying the coating film is not particularly limited. Methods for drying the coated film include, for example, natural drying, heat drying, hot air drying, and vacuum drying. The drying temperature and drying time of the coating film are not particularly limited and are set appropriately according to the thickness of the coating film, the amount of organic solvent in the coating film, etc. One example of drying conditions is heating at 100°C for 1 minute.

[0129] The curing conditions are not particularly limited. The curing temperature and curing time are set appropriately according to, for example, the composition of the specific (meth)acrylic copolymer and the type of crosslinking agent. For example, a curing temperature of 23°C to 50°C is preferable. The recovery period can range from 24 hours to 1 month, for example. Examples of curing conditions include one week at an ambient temperature of 23°C or one week at an ambient temperature of 40°C.

[0130] [License plate] The license plate of this disclosure comprises a plate base material and an overlaminate film of this disclosure provided on one side of the plate base material. The license plates described herein are equipped with the overlaminate film described herein, and therefore are less prone to appearance defects due to the use of the overlaminate film. Hereinafter, in the license plate of this disclosure, the "adhesive layer formed by the adhesive composition of this disclosure" that is present in the overlaminate film of this disclosure will also be referred to as the "first adhesive layer."

[0131] The embodiments of the license plate of this disclosure are not particularly limited, as long as they comprise a plate base material and an overlaminate film of this disclosure provided on one side of the plate base material. However, for example, an embodiment is preferred in which the surface protective film provided on the overlaminate film of this disclosure is provided as the outermost layer of the license plate. Embodiments of the license plate of the present disclosure may, for example, be an embodiment in which the side of the first adhesive layer of the overlaminate film of the present disclosure is attached to one side of the plate substrate, or an embodiment in which an image-receiving layer capable of forming a decorative layer on its surface is provided between the plate substrate and the overlaminate film of the present disclosure. The image receiving layer may constitute an image receiving film together with a second adhesive layer that enables adhesion of the image receiving layer to the plate substrate. In this case, the image receiving layer preferably contains a polyurethane resin and a (meth)acrylic resin, for example, from the viewpoint of providing low-temperature impact resistance and printability. Furthermore, the image receiving layer preferably further contains a white pigment, from the viewpoint of further improving whiteness. The second adhesive layer preferably contains a (meth)acrylic resin, for example, from the viewpoint of improving weather resistance, durability and adhesion to the plate substrate. Furthermore, the second adhesive layer preferably further contains a pigment, from the viewpoint of improving the appearance of the license plate. If the license plate according to this disclosure has an image-receiving layer, a decorative layer may be provided on the image-receiving layer as appropriate. In this case, the decorative layer is a layer provided to give the license plate an aesthetic appearance and is a layer that expresses patterns, designs, etc. As a method for forming a printed image on the image-receiving layer, known printing methods such as inkjet printing, screen printing, and gravure printing can be applied. For example, a layer on the image-receiving layer may be provided as a decorative layer, on which a design has been formed by inkjet printing.

[0132] Figure 2 is a schematic cross-sectional view showing an example of the configuration of the license plate of this disclosure. The license plate 40 shown in Figure 2 comprises a plate base material 50 and an overlaminate film 10 provided on one side of the plate base material 50. The overlaminate film 10 comprises a surface protection film 20 and a first adhesive layer 30 provided on one side of the surface protection film 20. In the license plate 40, the side of the overlaminate film 10 facing the first adhesive layer 30 is in contact with one side of the plate base material 50. The license plate 40 also has a decorative layer 60 on the surface protection film 20 that constitutes the overlaminate film 10.

[0133] Figure 3 is a schematic cross-sectional view showing an example of another configuration of the license plate of this disclosure. The license plate 70 shown in Figure 3 comprises a plate base material 50, an image receiving film 100 having an image receiving layer 80 and a second adhesive layer 90, and an overlaminate film 10 of the present disclosure. The overlaminate film 10 comprises a surface protection film 20 and a first adhesive layer 30 provided on one side of the surface protection film 20. In the license plate 70, the side of the image receiving film 100 facing the second adhesive layer 90 is in contact with one side of the plate base material 50. Also, in the license plate 70, the side of the overlaminate film 10 facing the first adhesive layer 30 is in contact with the side of the image receiving film 100 facing the image receiving layer 80. The license plate 70 has a decorative layer 60 on the surface protective film 20 that constitutes the overlaminate film 10. Furthermore, the license plate 70 has a decorative layer 60 on the image receiving layer 80 that constitutes the image receiving film 100. Details of the plate substrate 50 will be described later. Details of the overlaminate film 10, decorative layer 60, and image receiving film 100 are as previously described.

[0134] A metal plate or a resin plate can be used as the plate base material. Examples of metal sheets include aluminum sheets, stainless steel sheets, and iron sheets. Examples of resin sheets include polycarbonate sheets, polyester sheets, polyvinyl chloride sheets, acrylic sheets, ABS sheets, and PP sheets. The plate base material may be a metal plate or resin plate molded into a frame or the like.

[0135] The method for manufacturing license plates described herein is not particularly limited. The license plates described herein can be manufactured, for example, by the following method: First, the overlaminate film of this disclosure is bonded to a plate substrate before embossing with letters or the like. Next, the plate substrate to which the overlaminate film of this disclosure has been bonded is heated, and then the plate substrate is embossed, or the plate substrate to which the overlaminate film of this disclosure has been bonded is embossed while being heated. By doing so, the license plate of this disclosure can be manufactured. [Examples]

[0136] The adhesive compositions of this disclosure will be described in more detail below with reference to examples. This disclosure is not limited to the following examples unless it exceeds the spirit of the disclosure.

[0137] [Production of (meth)acrylic copolymer A] [Manufacturing example A-1] In a reactor equipped with a stirrer, reflux condenser, sequential dropper, and thermometer, 25% by mass of a monomer mixture consisting of 53.0 parts by mass of n-butyl acrylate (n-BA), 43.0 parts by mass of methyl acrylate (MA), and 4.0 parts by mass of acrylic acid (AA), along with 45.0 parts by mass of ethyl acetate [organic solvent] and 0.015 parts by mass of 2,2'-azobisisobutyronitrile [AIBN; polymerization initiator] were added and heated, and polymerization was carried out at reflux temperature for 20 minutes. Next, to the polymerization reaction product in a reactor maintained at reflux temperature, 75% by mass of the remaining monomer mixture, a polymerization initiator solution consisting of 30.0 parts by mass of ethyl acetate and 0.15 parts by mass of 2,2'-azobisisobutyronitrile was sequentially added dropwise over 1.5 hours, and the polymerization reaction was allowed to proceed for 1 hour. Then, a polymerization initiator solution consisting of 25.0 parts by mass of ethyl acetate and 0.30 parts by mass of 2,2'-azobisisobutyronitrile was sequentially added dropwise over 1 hour, and the polymerization reaction was allowed to proceed for a further 2 hours to obtain the polymerization reaction product. The obtained polymerization reaction product was diluted to a solid content concentration of 35% by mass using methyl ethyl ketone (MEK), cooled, and a solution of (meth)acrylic copolymer A-1 was obtained.

[0138] Here, "solids concentration" refers to the mass ratio of (meth)acrylic copolymer A-1 to the solution of (meth)acrylic copolymer A-1. The same applies to the solutions of (meth)acrylic copolymers A-2 to A-13 prepared below.

[0139] [Manufacturing examples A-2 to A-13] In production examples A-2 to A-13, the same procedure as in production example A-1 was followed, except that the monomer composition of (meth)acrylic copolymer A was changed to the monomer composition shown in Table 1, to obtain solutions of (meth)acrylic copolymer A-2 to A-13 with a solid content concentration of 35% by mass.

[0140] Table 1 shows the monomer composition [unit: mass%] and glass transition temperature (denoted as "Tg") [unit: °C] of (meth)acrylic copolymers A-1 to A-13. The weight-average molecular weight of all (meth)acrylic copolymers A-1 to A-13 was 600,000.

[0141] The glass transition temperatures of (meth)acrylic copolymers A-1 to A-13 were determined using the same method as described above for determining the glass transition temperature of (meth)acrylic copolymer (A). The weight-average molecular weights of (meth)acrylic copolymers A-1 to A-13 were measured using the same method as described above for measuring the weight-average molecular weight of (meth)acrylic copolymer (A).

[0142] Of the (meth)acrylic copolymers A-1 to A-13, (meth)acrylic copolymers A-1 to A-9 correspond to (meth)acrylic copolymer (A) in this disclosure.

[0143] [Table 1]

[0144] Details of each monomer listed in Table 1 are as follows: <(meth)acrylate alkyl monomer> "n-BA": n-butyl acrylate "MA": Methyl acrylate "2EHA": 2-ethylhexyl acrylate <Monomers containing a carboxyl group> "AA": Acrylic acid

[0145] In Table 1, a "-" in the monomer composition column indicates that the monomer corresponding to that column was not used.

[0146] [Production of (meth)acrylic copolymer B] [Manufacturing example B-1] In a reactor equipped with a stirrer, reflux condenser, sequential dropper, and thermometer, 20% by mass of a monomer mixture consisting of 80.0 parts by mass of methyl methacrylate (MMA), 14.0 parts by mass of ethyl acrylate (EA), and 6.0 parts by mass of 2-dimethylaminoethyl methacrylate (DM), along with 45.0 parts by mass of ethyl acetate [organic solvent] and 0.15 parts by mass of 2,2'-azobisisobutyronitrile [AIBN; polymerization initiator] were added and heated, and polymerization was carried out at reflux temperature for 20 minutes. In a reactor maintained at reflux temperature, 80% by mass of the remaining monomer mixture, a polymerization initiator solution consisting of 30.0 parts by mass of ethyl acetate and 0.15 parts by mass of 2,2'-azobisisobutyronitrile, were sequentially added dropwise over 1.5 hours to the polymerization reaction product. After holding for 1 hour, a polymerization initiator solution consisting of 25.0 parts by mass of ethyl acetate and 0.30 parts by mass of 2,2'-azobisisobutyronitrile was sequentially added dropwise over 1 hour, and the polymerization reaction was continued for a further 2 hours to obtain the polymerization reaction product. The obtained polymerization reaction product was diluted to a solid content concentration of 36% by mass using methyl ethyl ketone (MEK), cooled, and a solution of (meth)acrylic copolymer B-1 was obtained.

[0147] Here, "solids concentration" refers to the mass ratio of (meth)acrylic copolymer B-1 to the solution of (meth)acrylic copolymer B-1. The same applies to the solutions of (meth)acrylic copolymers B-2 to B-5 prepared below.

[0148] [Manufacturing examples B-2 to B-5] In production examples B-2 to B-5, the same procedure as in production example B-1 was followed, except that the monomer composition of (meth)acrylic copolymer B was changed to the monomer composition shown in Table 2, to obtain solutions of (meth)acrylic copolymers B-2 to B-5, each with a solid content concentration of 36% by mass.

[0149] Table 2 shows the monomer composition [unit: mass%] and glass transition temperature (denoted as "Tg") [unit: °C] of (meth)acrylic copolymers B-1 to B-5. The weight-average molecular weight of all (meth)acrylic copolymers B-1 to B-5 was 100,000.

[0150] The glass transition temperatures of (meth)acrylic copolymers B-1 to B-5 were determined using the same method as described above for determining the glass transition temperature of (meth)acrylic copolymer (A). The weight-average molecular weights of (meth)acrylic copolymers B-1 to B-5 were measured using the same method as described above for measuring the weight-average molecular weight of (meth)acrylic copolymer (A).

[0151] Of the (meth)acrylic copolymers B-1 to B-5, (meth)acrylic copolymers B-1 to B-4 correspond to (meth)acrylic copolymer (B) in this disclosure.

[0152] [Table 2]

[0153] Details of each monomer listed in Table 2 are as follows. <(meth)acrylate alkyl monomer> "MMA": Methyl methacrylate "EA": Ethyl acrylate <Monomers containing an amino group> "DM": 2-dimethylaminoethyl methacrylate "DE": 2-diethylaminoethyl methacrylate

[0154] In Table 2, a "-" in the monomer composition column indicates that the monomer corresponding to that column was not used.

[0155] [Preparation of adhesive composition] [Example 1A] 100 parts by mass (based on solid content) of (meth)acrylic copolymer A-1, 15 parts by mass (based on solid content) of (meth)acrylic copolymer B-1, and 0.05 parts by mass (based on solid content) of an epoxy crosslinking agent (product name: TETRAD-C, manufactured by Mitsubishi Gas Chemical Co., Ltd.) were stirred and mixed to obtain the adhesive composition of Example 1A.

[0156] [Examples 2A to 17A] In Examples 2A to 17A, the same procedure as in Example 1A was followed, except that the composition of the adhesive composition was changed to the composition shown in Table 3, to obtain each of the adhesive compositions of Examples 2A to 17A.

[0157] [Comparative Examples 1A-8A] In Comparative Examples 1A to 8A, the same procedure as in Example 1A was followed, except that the composition of the adhesive composition was changed to the composition shown in Table 4, to obtain each of the adhesive compositions of Comparative Examples 1A to 8A.

[0158] [Example 1B] The adhesive composition of Example 1B was obtained by stirring and mixing 100 parts by mass (solid content) of (meth)acrylic copolymer A-1, 15 parts by mass (solid content) of (meth)acrylic copolymer B-1, and 3.3 parts by mass (solid content) of an isocyanate-based crosslinking agent (product name: Takenate D-140N, manufactured by Mitsui Chemicals, Inc.) as a crosslinking agent.

[0159] [Examples 2B-17B] In Examples 2B to 17B, the same procedure as in Example 1B was followed, except that the composition of the adhesive composition was changed to the composition shown in Table 5, to obtain each of the adhesive compositions in Examples 2B to 17B.

[0160] [Comparative Examples 1B to 9B] In Comparative Examples 1B to 9B, the same procedure as in Example 1B was followed, except that the composition of the adhesive composition was changed to the composition shown in Table 6, to obtain each of the adhesive compositions of Comparative Examples 1B to 9B.

[0161] Tables 3 to 6 show the composition of the adhesive compositions for Examples 1A to 17A, Examples 1B to 17B, Comparative Examples 1A to 8A, and Comparative Examples 1B to 9B, the number of moles of carboxyl groups in (meth)acrylic copolymer A [unit: mmol], the number of moles of crosslinkable reactive groups (epoxy groups or isocyanate groups) in the crosslinking agent (epoxy crosslinking agent or isocyanate crosslinking agent) [unit: mmol], and the ratio of the number of moles of crosslinkable reactive groups in the crosslinking agent to the number of moles of carboxyl groups in (meth)acrylic copolymer A [indicated in the table as "number of moles of epoxy groups in the crosslinking agent / number of moles of carboxyl groups in (meth)acrylic copolymer A" or "number of moles of isocyanate groups in the crosslinking agent / number of moles of carboxyl groups in (meth)acrylic copolymer A"].

[0162] [Table 3]

[0163] [Table 4]

[0164] [Table 5]

[0165] [Table 6]

[0166] Details of the components listed in Tables 3 to 6 are as follows. <Crosslinking agent> "TETRAD-C" [Product name, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, epoxy equivalent: 100, solids content 100% by mass, manufactured by Mitsubishi Gas Chemical Company, Inc.] "TETRAD-X" [Product name, N,N,N',N'-tetraglycidyl-m-xylylenediamine, epoxy equivalent: 100, solids content 100% by mass, manufactured by Mitsubishi Gas Chemical Company, Inc.] "D-140N" [Takenate D-140N (product name), an adduct of isophorone diisocyanate (IPDI) and trimethylolpropane (TMP), solid content: 75% by mass, isocyanate group content (catalog value): 10.5% by mass, manufactured by Mitsui Chemicals, Inc.] "E405-70B" [Duranate E405-70B (product name), an adduct of hexamethylene diisocyanate (HMDI) and trimethylolpropane (TMP), solid content: 70% by mass, isocyanate group content (catalog value): 6.2% by mass, manufactured by Asahi Kasei Corporation] The above terms, "Takenate" and "Duranate," are both registered trademarks.

[0167] [Preparation of the base film] <Preparation of base film 1> In a reactor equipped with a stirrer, 90 parts by mass of polyurethane resin 1 [product name: Rezamin NE-8836, one-component curing polycarbonate-based urethane resin, manufactured by Dainichi Seika Kogyo Co., Ltd.], 10 parts by mass of polyurethane resin 2 [product name: Rezamin NE-8811, one-component curing polycarbonate-based urethane resin, manufactured by Dainichi Seika Kogyo Co., Ltd.], 20 parts by mass of crosslinking agent [product name: Rezamin X-100, isocyanate-based crosslinking agent, manufactured by Dainichi Seika Kogyo Co., Ltd.], 0.1 parts by mass of crosslinking catalyst [product name: UA-38, 2-ethylhexyl tin, manufactured by Tokushiki Co., Ltd.], and diluent solvent [N,N-dimethylformamide] were stirred and mixed for 10 minutes using a disperser at an ambient temperature of 23°C to obtain a base film forming composition. Next, a base film forming composition was applied to the easily peeled surface of a release film [product name: P756050, polyethylene terephthalate (PET), thickness: 75 μm, manufactured by Lintec Corporation] that had been surface-treated with a silicone-based release agent (so-called easy-peel treatment), so that the thickness after drying would be 35 μm, and a coating film was formed. Then, the formed coating film was heated at 100°C for 3 minutes, and then further heated at 160°C for 3 minutes to dry it, thereby producing base film 1 (urethane-based film). The above-mentioned "Rezamin" is a registered trademark.

[0168] <Preparation of base film 2-4> The following films were used as base films 2 to 4. • Base film 2: Vinyl chloride film (08C040M (manufactured by Nippon Carbide Industries Co., Ltd.)) • Base film 3: Acrylic film (HBD002 (manufactured by Mitsubishi Chemical Corporation)) • Base film 4: Fluorine-based film (14S0250 (manufactured by Denka Co., Ltd.))

[0169] [Preparation of adhesive film for evaluation] Using the adhesive compositions from Examples 1A to 17A, Examples 1B to 17B, Comparative Examples 1A to 8A, and Comparative Examples 1B to 9B, and the base films 1 to 4, evaluation adhesive films were prepared as follows. A release film [product name: PET75GS, material: polyethylene terephthalate (PET), thickness: 75 μm, manufactured by Lintec Corporation] that had been surface-treated with a silicone-based release agent (so-called easy-release treatment) was coated with an adhesive composition to form a coating film with a dry thickness of 3 μm, 12 μm, or 39 μm. The formed coating film was then dried by heating at 100°C for 1 minute to form an adhesive layer on the release film. Next, a base film was laminated to the exposed surface of the adhesive layer, and then cured under the conditions described below to produce an evaluation adhesive film having the structure of base film (so-called surface protection film) / adhesive layer / release film. The curing conditions were 40°C for 1 week for Examples 1A-17A and Comparative Examples 1A-8A, and 23°C for 1 week for Examples 1B-17B and Comparative Examples 1B-9B.

[0170] [Preparation of the substrate] A printed plate was prepared as the substrate to be used for evaluation testing. Specifically, it was prepared according to the following procedures (1) to (3).

[0171] (1) Formation of the image-receiving layer In a reactor equipped with a stirrer, 100 parts by mass of polyurethane resin [product name: Rezamin NE-8811, one-component curing polycarbonate-based urethane resin, manufactured by Dainichi Seika Kogyo Co., Ltd.], 15 parts by mass of (meth)acrylic resin [product name: Dianaal MB-2593, methacrylic resin, manufactured by Mitsubishi Chemical Corporation], 42 parts by mass of pigment [product name: NX-501, titanium dioxide, manufactured by Dainichi Seika Kogyo Co., Ltd.], and a diluent solvent [a mixed solvent of isopropyl alcohol and toluene (volume ratio 1:1)] were stirred and mixed for 10 minutes using a disperser at an ambient temperature of 23°C to obtain a composition for forming an image-receiving layer. Next, an image-receiving layer-forming composition was applied to the easily-peeled surface of a release film [product name: P756050, polyethylene terephthalate (PET), thickness: 75 μm, manufactured by Lintec Corporation] that had been surface-treated with a silicone-based release agent (so-called easy-peel treatment), so that the thickness after drying would be 55 μm, thereby forming a coated film. Then, the formed coated film was heated in a hot air circulation dryer at 100°C for 3 minutes, and then further heated at 160°C for 3 minutes to dry it, thereby forming an image-receiving layer on the release film. Please note that "Rezamin" and "Dianal" are registered trademarks.

[0172] (2) Formation of the second adhesive layer A composition for forming the second adhesive layer was obtained by stirring and mixing 100 parts by mass of an acrylic copolymer obtained by polymerizing 90 parts by mass of n-butyl acrylate and 10.0 parts by mass of acrylic acid, 8.34 parts by mass of a white pigment [product name: DAD-100, component: titanium dioxide, manufactured by DIC Corporation], 5.0 parts by mass of an isocyanate crosslinking agent [product name: Coronate L-45E, manufactured by Mitsubishi Gas Chemical Company, Inc.], and a diluent [ethyl acetate]. Next, the composition for forming the second adhesive layer was applied to the easily peeled surface of a release film [product name: PET75GS, material: polyethylene terephthalate (PET), thickness: 75 μm, manufactured by Lintec Corporation] that had been surface-treated with a silicone-based release agent (so-called easy-peel treatment) to form a coated film with a dry thickness of 40 μm. Next, the formed coating film was dried by heating it at 100°C for 1 minute using a hot air circulation dryer, thereby forming a second adhesive layer on the release film. Please note that "Coronate" is a registered trademark.

[0173] (3) Preparation of printing plates An image-receiving film was fabricated by bonding the exposed surface of the image-receiving layer formed above to the exposed surface of the second adhesive layer. Next, under ambient temperature of 23°C and 50% RH, the release film on the second adhesive layer side of the image-receiving film was peeled off, and the exposed surface of the second adhesive layer was bonded to an aluminum plate. Then, the release film on the image-receiving layer side of the image-receiving film was peeled off, and a solid cyan and yellow print was applied to the exposed surface of the image-receiving layer using an inkjet printer (model number: JV-300, manufactured by Mimaki Engineering Co., Ltd.) to form a decorative layer. In this way, a printed plate having the configuration of decorative layer / image-receiving layer / second adhesive layer / aluminum plate was fabricated.

[0174] [evaluation] 1. Adhesive strength The evaluation adhesive film prepared as described above was cut to a size of 25 mm x 150 mm (long side), and the release film was peeled off. Next, the side of the adhesive layer exposed by peeling was placed on the exposed side of the decorative layer on the printing plate prepared as described above, and then bonded by passing a 2 kg roller back and forth twice. The resulting laminate was then heat-treated at 120°C for 1 hour using a hot air circulation dryer to obtain a sample for adhesive strength evaluation testing. For this adhesion strength evaluation test sample, the adhesion strength (unit: N / 25mm) was measured when the evaluation adhesive film (composition: base film / adhesive layer) was peeled 180° along the long side (150mm) from the printing plate, using a method compliant with JIS Z 0237:2000. Specifically, a single-column type material testing machine [model number: RTG-1310] manufactured by A&D Co., Ltd. was used as the measuring device, and measurements were taken under conditions of an ambient temperature of 23°C, 50% RH, and a peeling speed of 300 mm / min. The adhesion strength to the adherend was then evaluated according to the evaluation criteria below. The results are shown in Tables 5 and 6. In the evaluation criteria below, "A" and "B" represent a usable level, with "A" being the most preferable.

[0175] -Evaluation Criteria- A: The adhesive strength is 15N / 25mm or more. B: The adhesive strength is 5N / 25mm or more and less than 15N / 25mm. C: The adhesive strength is less than 5N / 25mm.

[0176] 2. Appearance during three-dimensional molding 2-1. Cohesive failure The evaluation adhesive film prepared as described above was cut to a size of 50 mm x 50 mm, and the release film was peeled off. Next, the surface of the adhesive layer exposed by peeling was placed on the exposed surface of the decorative layer on the printing plate prepared as described above, and then bonded by passing a 2 kg roller back and forth twice. The laminate obtained by this bonding was heat-treated at 120°C for 1 hour using a hot air circulation dryer to obtain a sample for cohesive failure evaluation test. A DuPont impact test was performed on this sample for cohesive failure evaluation from the aluminum plate side under the following conditions.

[0177] <DuPont Impact Test Conditions> Falling weight: 1kg Drop height: 50cm Receiving jig: recessed R shape 1 / 4 inch Impact point: Flat tip shape, 1 / 2 inch diameter, 3 / 8 inch tip diameter

[0178] After the test, the stretched and deformed portions of the evaluation adhesive film (composition: base film / adhesive layer) were observed using an optical microscope. The presence and extent of air bubbles in the adhesive layer were then checked, and the state of cohesive failure was evaluated according to the evaluation criteria below. The results are shown in Tables 7 and 8. The formation of bubbles in the adhesive layer indicates that cohesive failure is occurring in the adhesive layer. In the evaluation criteria below, "A" and "B" represent a usable level, with "A" being the most preferable.

[0179] -Evaluation Criteria- A: No air bubbles were observed in the adhesive layer (see Figure 4A). B: A small amount of air bubbles were observed in the adhesive layer (see Figure 4B). C: Significant bubble formation is observed in the adhesive layer (see Figure 4C).

[0180] 2-2. Distortion The evaluation adhesive film prepared as described above was cut to a size of 60 mm x 90 mm, and the release film was peeled off. Next, the surface of the adhesive layer exposed by peeling was placed on the exposed surface of the decorative layer on the printing plate prepared as described above, and then bonded by passing a 2 kg roller back and forth twice. The resulting laminate was then subjected to a heat treatment at 120°C for 1 hour using a hot air circulation dryer to obtain a sample for strain evaluation testing. For this strain evaluation test sample, embossing was performed using a Hydraulic Embossing Press P50 (manufactured by JHTOENNJES) at a press pressure of 60 bar, using a die measuring 60 mm x 90 mm. The die used for the press work, as outlined in Figure 5, had a raised section with a width of 4.0 mm and a height of 1.9 mm, mimicking the bead portion of a vehicle registration number plate used in Japan for automobiles (including motorcycles and mopeds). The bead portion refers to the embossed area on the edge of the number plate. Next, the embossed sample for distortion evaluation testing was heated at 125°C for 8 minutes. After heating, the convex portion was observed with an optical microscope, and the presence or absence of distortion was checked according to the evaluation criteria below. The results are shown in Table 9. Note that "distortion" in the convex portion refers to the condition in which streaky wrinkles appear around the convex portion. In the evaluation criteria below, "A" and "B" represent a usable level, with "A" being the most preferable. A: No distortion can be observed at all in the convex portion. B: A slight distortion can be observed in the convex portion. C: Distortion can be observed throughout the convex portion.

[0181]

Table 7

[0182]

Table 8

[0183]

Table 9

[0184] As shown in Table 7 and Table 8, it was confirmed that the pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of the examples has high adhesive force to the adherend. It was also confirmed that the pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of the examples is less prone to cohesive failure around the convex portion of the adherend during three-dimensional molding, and less likely to cause poor appearance.

[0185] On the other hand, as shown in Table 7 and Table 8, it was confirmed that the pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of the comparative examples is inferior to the pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of the examples in terms of the adhesive force to the adherend or the evaluation result of cohesive failure around the convex portion of the adherend during three-dimensional molding.

[0186] In addition, as shown in Table 9, it can be seen that the occurrence of strain is easily suppressed by using a urethane-based film as the base film.

Description of Reference Signs

[0187] 10: Overlaminate Film 20: Surface Protective Film 30: Pressure-Sensitive Adhesive Layer (First Pressure-Sensitive Adhesive Layer) 40, 70: License Plate 50: Plate Substrate 60: Decorative Layer 80: Image Receiving Layer 90: Second Pressure-Sensitive Adhesive Layer 100: Image Receiving Film

Claims

1. A surface protective film containing a polyurethane resin, An adhesive layer provided on one side of the surface protective film, A license plate overlaminate film comprising: The adhesive layer comprises a (meth)acrylic copolymer (A), a (meth)acrylic copolymer (B), and an epoxy crosslinking agent. Includes, The (meth)acrylic copolymer (A) contains constituent units derived from monomers having carboxyl groups in a proportion of 1% to 15% by mass relative to the total constituent units of the (meth)acrylic copolymer (A), and has a glass transition temperature of -45°C to -5°C. The (meth)acrylic copolymer (B) contains constituent units derived from a monomer having at least one amino group selected from the group consisting of primary amino groups, secondary amino groups, and tertiary amino groups, and has a glass transition temperature of 50°C to 100°C. The content of the (meth)acrylic copolymer (B) is 5 to 25 parts by mass per 100 parts by mass of the (meth)acrylic copolymer (A), An overlaminate film for license plates, formed from an adhesive composition in which the ratio of the number of moles of epoxy groups in the epoxy crosslinking agent to the number of moles of carboxyl groups in the (meth)acrylic copolymer (A) is 0.0045 or more.

2. A surface protective film containing a polyurethane resin, An adhesive layer provided on one side of the surface protective film, A license plate overlaminate film comprising: The adhesive layer comprises a (meth)acrylic copolymer (A), a (meth)acrylic copolymer (B), and an isocyanate crosslinking agent. Includes, The (meth)acrylic copolymer (A) contains constituent units derived from monomers having carboxyl groups in a proportion of 1% to 15% by mass relative to the total constituent units of the (meth)acrylic copolymer (A), and has a glass transition temperature of -45°C to -5°C. The (meth)acrylic copolymer (B) contains constituent units derived from a monomer having at least one amino group selected from the group consisting of primary amino groups, secondary amino groups, and tertiary amino groups, and has a glass transition temperature of 50°C to 100°C. The content of the (meth)acrylic copolymer (B) is 5 to 25 parts by mass per 100 parts by mass of the (meth)acrylic copolymer (A), An overlaminate film for license plates, formed from an adhesive composition in which the ratio of the number of moles of isocyanate groups in the isocyanate crosslinking agent to the number of moles of carboxyl groups in the (meth)acrylic copolymer (A) is 0.1 to 0.

5.

3. The overlaminate film for license plates according to claim 1 or claim 2, wherein the weight-average molecular weight of the (meth)acrylic copolymer (A) is 400,000 to 2,500,000.

4. The overlaminate film for license plates according to claim 1 or claim 2, wherein the weight-average molecular weight of the (meth)acrylic copolymer (B) is 0.5 million to 200,000.

5. The license plate overlaminate film according to claim 1 or claim 2, wherein the total content of constituent units derived from the monomer having an amino group in the (meth)acrylic copolymer (B) is 1.5% by mass or more relative to the total constituent units of the (meth)acrylic copolymer (B).

6. Plate substrate and An overlaminate film for license plates according to claim 1 or claim 2 is provided on one side of the plate substrate, A license plate equipped with [a specific feature / feature].

7. The license plate according to claim 6, further comprising an image receiving layer between the plate base material and the license plate overlaminate film.

Citation Information

Patent Citations

  • License plate sheet, license plate laminate, and license plate

    JP2015530299A

  • Graphic film for license plate, and license plate comprising graphic film and manufacturing method therefor

    JP2016215672A

  • Graphic film for license plate, license plate and manufacturing method therefor

    JP2017177481A

  • Adhesive composition for film and adhesive sheet

    JP2018123224A

  • Adhesive composition for decorative film, decorative film and decorative molded product

    JP2019073641A